Online Marketing Through Digital Marketing Platform for Micro, Small, and Medium Enterprises Bamboo Craftsmen in Sukolilo Village, Lamongan, East Java - Wahidahwati, Wahidahwati; Rahayu, Rika; Zahro, Maratus; Maryam, Dewi; Kirana, Ardilla Ayu (CV Firmos, 2025)
In the face of increasingly difficult economic challenges, Micro, Small and Medium Enterprises (MSMEs), especially bamboo craftsmen, are faced with the need to sell and market products online in order to survive. Although many products produced by bamboo artisan MSMEs have quality, the limited location far from the city center and the lack of understanding about online sales cause a lack of interest from consumers. Therefore, the purpose of this service program is to provide training and assistance to MSMEs in Sukolilo Village, Lamongan, especially bamboo craftsmen, in using digital marketing strategies by utilizing the Shopee platform. The community service implementation method consists of 4 stages, namely identification, training and mentoring, monitoring and evaluation, and the impact of the community service. The results of the community service found that this digital marketing strategy can provide various benefits, ranging from increasing brand awareness to increasing online sales turnover. The implementation of digital marketing involves the stages of partner surveys, training and mentoring, the creation of social media specifically for MSME Bamboo Craftsmen in Sukolilo Village, Lamongan Regency, and evaluation of the implementation of digital marketing to expand sales reach and maintain business continuity amidst competition and the current sluggish economic conditions. The impact of this community service is that bamboo craftsmen understand the importance of digital marketing.